Utilization of Snail (Achatina fulica) Shell Waste for Synthesis of Calcium Tartrate Tetrahydrate (CaC4H4O6.4H2O) Single Crystals in Silica Gel - Yuniar P Prananto; Mohammad M Khunur; Rachmat T Tjahjanto; Imam Sakdi; Muchammat C Basori (Journal of Tropical Life Science, 2012)
Snail (Achatina fulica) shell waste is massively produced by many home industries in Indonesia, especially in East Java. The snail shell is known for high calcium; therefore it is potential to be used as calcium source of supernatant in the synthesis of piezoeletric material, such as single crystal of calcium tartrate tetrahydrate (CaTT). The aim of this research is to study the synthesis and characterization of CaTT or CaC4H4O6.4H2O from snail shell waste in silica gel. Supernatant solution of CaCl2 was prepared from CaO, which previously made by calcinating the shell at 1000°C, and then reacted with HCl 1.5M. Synthesis of CaTT was conducted in a single-tube reaction at room temperature in which silica gel was used as growth medium with gelling time of 10 days and growth time of 2 weeks. The pH of gel and CaCl2 concentration were varied, 3.00; 3.50; 4.00; 4.50; 5.00; and 0.27; 0.36; 0.45; 0.54 M respectively, in order to obtain optimum condition of the synthesis, which is indicated from crystal yields. The synthesized crystals were characterized by atomic adsorption spectrophotometry (AAS), infrared spectroscopy (IR) and powder X-ray diffraction (XRD). Experimental data shows that optimum condition was obtained at pH of 3.50 and [CaCl2] of 0.45M with yield of 69.37%. The obtained single crystal has clear color and octahedral-like shape with size ranged between 4 - 9 mm. Analysis data by FTIR and powder XRD confirmed that the obtained crystal was CaTT single crystals with crystal system of orthorhombic.